Social media and self-resilience during pandemics: experiences from youth volunteers in Rwanda - Bimenyimana Pierre Celestin; Ronald Mayora Synnes; Rutembesa Eugene; Paul Bukuluki (Discover Social Science and Health)
Abstract The current study intends to investigate how social media may have played a considerable role in the youth volunteers’ self-resilience during the hard times of the COVID-19 pandemic in the Huye district of Rwanda. This study adopted a qualitative approach. Data were collected through 21 interviews with youth volunteers, local leaders, leaders from the central government, and opinion leaders among citizens of the Huye district in Rwanda selected on a network and purposive sampling bases. The data analysis followed a narrative thematic analysis inspired by four elements of self-resilience by Jurgens and Helsloot. The findings revealed that social media were instrumental in information gathering, information dissemination, facilitating collaborative problem-solving, and coping with new situations, such as how people managed to handle their daily initiatives without meeting physically. Nevertheless, there is an acknowledgment that social media can also, at times, act as a distraction rather than a beneficial tool in the context of a pandemic. The study brings insight into how social media can be effective in social work community interventions, especially working with young people.